Comparative Life Cycle Analysis of Materials in Wastewater Piping Systems. (2015) - Vahidi, Ehsan; Jin, Enze; Das, Maithilee; Singh, Mansukh; Zhao, Fu
Abstract: Over the past decades, dramatic increases in population and quality of life have led to an ever-growing need for wastewater infrastructure systems. Designing and applying novel pipelines with lower installation and long-term operation and maintenance expense will become crucial in the near future for the implementation of the best environmental management strategies. In this paper, a comparative life cycle analysis (LCA) was performed for four different types of wastewater pipe materials: composite fiber reinforced Polymer (FRP), PVC, ductile iron, and concrete. The functional unit in our analysis was defined as the infrastructure needed for the collection and transportation of one cubic meter of waste water from a city for a period of 50 years. Assuming a city that has a population of 200, 000 and generates 0.3 cubic meter of wastewater per person per day, the reference flow for the above assumed functional unit can be deduced. Considering various life cycle stages, environmental impacts such as "ozone layer depletion", eco-toxicity", and "energy consumption" were quantified and compared for all pipe materials. The results show the production phase has the maximum impact among the different phases of all pipe manufacturing and within different environmental impacts; fossil fuel is the largely affected area in all piping systems and among the four pipes, ductile iron has the maximum impact and PVC has the minimum impact on most of these areas.